2020
DOI: 10.3390/ijerph17020511
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported General Health, Overall and Work-Related Stress, Loneliness, and Sleeping Problems in 335,625 Swedish Adults from 2000 to 2016

Abstract: The prevalence of poor health, in particular stress-related mental ill-health, is increasing over time and birth cohorts. As rapid societal changes have occurred in the last decade and still are occurring, there is an interest in investigating the trends in health-related factors. The aim of the present study was to investigate trends in self-reported general health, overall stress, work-related stress, feelings of loneliness, and sleeping problems in 335,625 Swedish adults across categories of gender, geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…On a population level, our findings are consistent with recent data from Sweden reporting that adults, and young adults in particular, experienced an increase in poor sleep, stress and poorer general health from 2000 to 2016 ( Blom et al, 2020 ). Data from US adults also suggest increased levels of stress, with work and money articulated as the most common reasons for anxiety ( American Psychological Association, 2014 , 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…On a population level, our findings are consistent with recent data from Sweden reporting that adults, and young adults in particular, experienced an increase in poor sleep, stress and poorer general health from 2000 to 2016 ( Blom et al, 2020 ). Data from US adults also suggest increased levels of stress, with work and money articulated as the most common reasons for anxiety ( American Psychological Association, 2014 , 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…A study aiming at investigating trends in self-reported general health, showed that the risk of having ≥3 symptoms increased significantly from 2000 to 2016 (179). The increases in symptoms were significantly higher in young and individuals with lower education (179). This is in accordance with our observation that the younger population reported more symptoms.…”
Section: Nutrition Impact Symptoms and Quality Of Lifesupporting
confidence: 89%
“…A previous study of self-reported somatic and psychological symptoms showed that women reported higher total symptom prevalence than men and a trend was found showing an increase in symptom reporting from 1985 and onwards (178). A study aiming at investigating trends in self-reported general health, showed that the risk of having ≥3 symptoms increased significantly from 2000 to 2016 (179). The increases in symptoms were significantly higher in young and individuals with lower education (179).…”
Section: Nutrition Impact Symptoms and Quality Of Lifementioning
confidence: 95%
“…Self-reported general health, defined as perceived overall physical and mental health, is associated with all-cause mortality and morbidity [ 21 , 22 ]. During the last decades poor self-reported general health has increased markedly in all age groups and education groups in the working population in Sweden, [ 23 ]. Studies indicate different relationships between domain specific sitting time (work, transport and leisure time) and self-reported quality of life [ 19 ] but to our knowledge, studies are lacking concerning domain specific sitting in the working population and its association with self-reported general health.…”
Section: Introductionmentioning
confidence: 99%